Effects of Teacher Intonation on the Response of Children with Autism. - Micke, Cierra A.; Drees, Cassandra C.; Rieck, Tasha M. (My University, 2009)
This study examined performance on maintenance skills when using a conversational or enthusiastic voice tone for children diagnosed with autism.
Effects of Teacher Intonation on the Responding of Young Children with Autism.
Color poster with text and graphs describing research conducted by Cassandra C. Drees, Tasha M. Rieck, and Cierra A. Micke, advised by Kevin P. Klatt.
Keywords: Voice--Psychological aspects; Intonation (Phonetics); Autistic children--Education; Autistic children--Case studies; Posters